The Relationship Between Stress Level And Menstrual Cycle In Final Level Of Sriwijaya University Medical Education Batch 2019 - Prasetya, Bagus Eko; Abadi, Adnan; Purnamasari, Septi (Fakultas Kedokteran Universitas Andalas, 2023)
Background: Menstruation is the discharge of blood and mucous tissue through the vaginafrom the uterus periodically every month with a span of 24-35 days. Menstruation can beaffected by stress. The burden of working on the final assignment coupled with learning thathas started to be done face to face makes students have to adjust to their daily habits. Thepurpose of this study was to find out whether there is a relationship between stress levels infinal year students of Sriwijaya University Medical Education class of 2019.Methods: This study uses a type of observational research, namely correlation analysis witha cross sectional approach. Data collection was carried out in October 2022 and obtained124 student data, then an analysis was carried out using the SPSS program and analyzedusing the Chi Square test.Results: From the results of the study, it was found that 124 respondents who experiencedmenstrual disorders were 47 (37.9%) while 77 (62.1%) experienced normal menstruation,then the most stress was severe stress, namely 43 (34.7). Then an analysis of the relationshipbetween stress and the menstrual cycle was carried out, the result was p = 0.009 / p <Î±(0.05), which means that there is a relationship between stress and the menstrual cycle.Conclusion: There is a relationship between stress levels and the menstrual cycle